The Impact of GDP on Foreign Direct Investment in Pakistan - Ali, Jafar; Shah, Syed Hidayat Ullah; Rahim, Tariq (The Lighthouse Journal of Social Sciences, 2024)
Foreign Direct Investment (FDI) is widely recognized as a catalyst for economic development, especially in emerging economies. However, in Pakistan, FDI inflows have remained inconsistent despite efforts to promote growth. This study investigates the relationship between Gross Domestic Product (GDP) and FDI in Pakistan to determine whether economic growth significantly attracts foreign investment. Using a dataset of 21 annual observations, the study applies correlation and linear regression analyses to assess the impact of GDP on FDI. The correlation coefficient between GDP and FDI is 0.1775, indicating a weak positive relationship. Regression analysis reveals that the coefficient for FDI is 0 (p = 0.243), suggesting that the effect of FDI on GDP is not statistically significant at the 5% level. The findings imply that while there is a weak association between GDP and FDI, other factors such as political stability, institutional quality, and infrastructure may play a more substantial role in influencing foreign investment decisions. The study concludes with policy recommendations focused on improving the investment climate beyond economic growth alone, in order to enhance FDI inflows sustainably.